Stroke and migraine is there a possible comorbidity?. Issue 1 (December 2016) - Spalice, Alberto; Del Balzo, Francesca; Papetti, Laura; Zicari, Anna; Properzi, Enrico; Occasi, Francesca; Nicita, Francesco; Duse, Marzia
Abstract The association between migraine and stroke is still a dilemma for neurologists. Migraine is associated with an increased stroke risk and it is considered an independent risk factor for ischaemic stroke in a particular subgroup of patients. The pathogenesis is still unknown even if several studies report some common biochemical mechanisms between these two diseases. A classification of migraine-related stroke that encompasses the full spectrum of the possible relationship between migraine and stroke includes three main entities: coexisting stroke and migraine, stroke with clinical features of migraine, and migraine-induced stroke. The concept of migraine-induced stroke is well represented by migrainous infarction and it is described in the revised classification of the International Headache Society (IHS), representing the strongest demonstration of the relationship between ischaemic stroke and migraine. A very interesting common condition in stroke and migraine is patent foramen ovale (PFO) which could play a pathogenetic role in both disorders. The neuroradiological evidence of subclinical lesions most typical in the white matter and in the posterior artery territories in patients with migraine, opens a new field of research. In conclusion the association between migraine and stroke remains an open question. Solving the above mentioned issues is fundamental to understand the epidemiologic, pathogenetic and clinical aspects of migraine-related stroke.